Standard specification for seamless austenitic steel pipe for high-temperature central-station service. (American Society for Testing and Materials, 2006)
This specification2 covers seamless austenitic steel pipe intended for high-temperature central-station service. Among the grades covered are five H grades and two nitrogen grades (304N and 316N) that are specifically intended for hightemperature service.